O impacto da pandemia de Covid-19 no risco de fragilidades em idosos atendidos no ambulatório de geriatria do hospital universitário João de Barros Barreto (HUJBB) - MONTEVERDE, Beatriz Tavares (2023)
The frailty syndrome has undergone several changes in its definition over the years, and today it stands out as a geriatric syndrome defined by the tripod: sarcopenia, neuroendocrine and immunological dysregulation. During the pandemic period, it was necessary to take social isolation measures to contain the transmission of the virus, taking special care with the age group over 60 years, as they were at greater risk of developing serious conditions and mortality. This study aimed to verify the risk of frailty in elderly people treated at the geriatrics outpatient clinic of the Hospital Universitário João de Barros Barreto (HUJBB) in a period of the COVID- 19 pandemic in the year 2022 through an observational quantitative cross-sectional study carried out with 100 elderly people of both sexes from 60 years of age and who agreed to participate in the research, signing the Free Informed Consent Term (FICT). The elderly were evaluated according to the index of clinical-functional vulnerability of the elderly (IVCF20) and variables related to sociodemographic characteristics and questions associated with the pandemic. It is observed that 57% of the patients were aged between 60-74 years, with the majority being female patients (75%). Of the sample, 26% had a low risk of frailty, 36% had a moderate risk and 38% had a high risk of frailty. The risk of frailty was significantly associated with age group (p=0.0286), loss of appetite during the pandemic (p=0.072) and feeling of weakness during the pandemic (p=0.0262). The most frequent comorbidities were systemic arterial hypertension (69%), diabetes mellitus (38%) and osteoarticular diseases (34%). No single comorbidity related to the risk of frailty had a statistically significant difference, with all associations showing p>0.05. Statistically, patients who reported a feeling of weakness and loss of appetite during the pandemic period showed a higher risk of frailty, unlike those who did not present such symptoms. Therefore, it is undeniable that the pandemic has left profound consequences in society, especially in the lives of older people, making them more prone to sarcopenia, low immunity, neuroendocrine dysregulation and, consequently, a greater risk of weakening. Therefore, the importance of classifying elderly patients regarding the risk of frailty at different levels of care is verified, seeking a better design of care for this population.